2012
DOI: 10.5194/bg-9-2989-2012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of nitrous oxide emissions in a mixed farming landscape of Denmark

Abstract: Abstract. Nitrous oxide (N 2 O) emissions from agricultural land are variable at the landscape scale due to variability in land use, management, soil type, and topography. A field experiment was carried out in a typical mixed farming landscape in Denmark, to investigate the main drivers of variations in N 2 O emissions, measured using static chambers. Measurements were made over a period of 20 months, and sampling was intensified during two weeks in spring 2009 when chambers were installed at ten locations or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…General correlations between trends in farm N-surplus and nitrate concentrations in Danish groundwater for the period 1950-2007 have been published by Hansen et al (2011Hansen et al ( , 2012, but the potential remains for further investigation of more detailed landscapelevel effects and correlations (Bende-Michl et al, 2011). In this context, the present results are promising for further investigation of correlations between the site-based N measurements carried out in the landscapes during the NitroEurope project (e.g., Schelde et al, 2012;Wohlfart et al, 2012;Vogt et al, 2012) and the geographical location of farms and derived N surplus and N sources from specific fields, livestock houses, manure stores, etc., as well as the transfer to N-sinks in the landscapes . There is further potential to protect sensitive semi-natural areas vulnerable to N pollution, not only through increasing N-efficiency but also via landscape-level spatial planning, by for example planting of hedgerows and trees along water courses (Christen and Dalgaard, 2012) or around near livestock facilities to re-capture or disperse ammonia emitted (Dragosits et al, 2006).…”
Section: Landscape-scale Measurements and Sustainable Farm N Managemementioning
confidence: 77%
See 1 more Smart Citation
“…General correlations between trends in farm N-surplus and nitrate concentrations in Danish groundwater for the period 1950-2007 have been published by Hansen et al (2011Hansen et al ( , 2012, but the potential remains for further investigation of more detailed landscapelevel effects and correlations (Bende-Michl et al, 2011). In this context, the present results are promising for further investigation of correlations between the site-based N measurements carried out in the landscapes during the NitroEurope project (e.g., Schelde et al, 2012;Wohlfart et al, 2012;Vogt et al, 2012) and the geographical location of farms and derived N surplus and N sources from specific fields, livestock houses, manure stores, etc., as well as the transfer to N-sinks in the landscapes . There is further potential to protect sensitive semi-natural areas vulnerable to N pollution, not only through increasing N-efficiency but also via landscape-level spatial planning, by for example planting of hedgerows and trees along water courses (Christen and Dalgaard, 2012) or around near livestock facilities to re-capture or disperse ammonia emitted (Dragosits et al, 2006).…”
Section: Landscape-scale Measurements and Sustainable Farm N Managemementioning
confidence: 77%
“…Nitrate concentrations were also measured periodically (up to 12 times per year) in the groundwater at up to 15 locations within three of the landscapes (DK, FR, and PL) and in stream water at up to nine locations within five of the landscapes (all except IT). See also Schelde et al (2012) and Wohlfart et al (2012) for more information about the monitoring designs, and Ullrich and Volk (2010) and Bende-Michl et al (2011) for a further discussion of sampling strategies and treatment of the variability in results, or Vogt et al (2012) for a detailed investigation of N budgets derived from measurements and modelling in the UK landscape.…”
Section: Verification Measurementsmentioning
confidence: 99%
“…These soil properties imply a partial immobilization of NO − 3 (Randall and Mulla, 2001;Schiff et al, 2002) and therefore lower concentrations in stream water. In the same area with organic soils along the southern branch, Schelde et al (2012) observed that ammonia was more abundant than NO − 3 in the organic soils, and they found emissions of nitrous oxide to be relatively low at the riparian organic soils. On the other hand, high positive correlations (0.87) between NO − 3 -N concentrations and soil properties were observed for coarse clayey sand that is predominant in the northern branch contributing area.…”
Section: Nitratementioning
confidence: 99%
“…4). In the described study area, Schelde et al (2012) Schelde et al (2012), denitrification is likely to play a dominating factor for N losses in the area.…”
Section: Nitratementioning
confidence: 99%
“…In recent decades, due to growing interest in phenomena caused by global warming, the quantity of studies on greenhouse gas emissions at watershed scale (Vilain et al 2012) and local to regional landscape scale (Le Mer and Roger 2001;Sozanska et al 2002;Lilly et al 2003, Sommer et al 2004Mander et al 2010;Wolf et al 2010;Nol et al 2012;Schelde et al 2012) has increased significantly.…”
mentioning
confidence: 99%